2018
DOI: 10.3390/ph11030085
|View full text |Cite
|
Sign up to set email alerts
|

Iron Absorption in Iron-Deficient Women, Who Received 65 mg Fe with an Indonesian Breakfast, Is Much Better from NaFe(III)EDTA than from Fe(II)SO4, with an Acceptable Increase of Plasma NTBI. A Randomized Clinical Trial

Abstract: Plasma non-transferrin-bound iron (NTBI) is potentially harmful due to the generation of free radicals that cause tissue damage in vascular and other diseases. Studies in iron-replete and iron-deficient subjects, receiving a single oral test dose of Fe(II)SO4 or NaFe(III)EDTA with water, revealed that FeSO4 was well absorbed when compared with NaFeEDTA, while only the Fe(II) compound showed a remarkable increase of NTBI. As NaFeEDTA is successfully used for food fortification, a double-blind randomized cross-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…To assess acute iron absorption from ferrous sulphate, it is advised to administer a dose yielding 65 mg of elemental iron and assess serum iron at 2–3 h post supplementation [ 67 , 68 ]. This method is used to evaluate gut iron absorption in humans [ 68 , 77 , 78 ]. If gut iron absorption is adequate, there is approximately a 17.9 µmol/L increase in serum iron levels as suggested by Alleyne et al [ 68 ] or an increase of two to three times above baseline levels [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…To assess acute iron absorption from ferrous sulphate, it is advised to administer a dose yielding 65 mg of elemental iron and assess serum iron at 2–3 h post supplementation [ 67 , 68 ]. This method is used to evaluate gut iron absorption in humans [ 68 , 77 , 78 ]. If gut iron absorption is adequate, there is approximately a 17.9 µmol/L increase in serum iron levels as suggested by Alleyne et al [ 68 ] or an increase of two to three times above baseline levels [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we chose dehulled lentils for Fe fortification, because an earlier study reported that lentil seed coat removal increases the relative Fe bioavailability [ 27 ]. This is because ferric iron has the highest binding stability with EDTA (ethylene diamine tetra-acetic acid) and EDTA thus protects from binding to iron absorption inhibitors [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fe-rich groundwater contains bioavailable Fe II . Whenever clean Fe-rich groundwater is available as a drinking water source, it suffices to stabilize Fe II , for example by addition of AA or lemon juice, to improve the Fe status of the population 25 , 40 , 41 .…”
Section: Background Of the Fe II -Aa Conceptmentioning
confidence: 99%
“…Fe 0 and Fe III sources are less soluble and their bioavailability is correspondingly low. In other words, soluble Fe should be present as stable Fe II to be absorbed by the human body 2 , 7 , 17 , 25 . This is the reason why the simultaneous consumption of Fe rich diets and vitamin C (ascorbic acid—AA) has consistently and successfully treated IDA 2 , 7 , 22 , 24 , 26 .…”
Section: Introductionmentioning
confidence: 99%